Microplastic-Mediated Heavy Metal Uptake in Lettuce (Lactuca sativa L.): Implications for Food Safety and Agricultural Sustainability - Bhakti Jadhav; Agnieszka Medyńska-Juraszek (Molecules)
This study investigates how different types of microplastics (MPs)—fibers, glitter, plastic bags, and plastic bottles—influence heavy metal uptake in lettuce (Lactuca sativa L.), a commonly consumed leafy vegetable. A controlled eight-week pot experiment was conducted in a greenhouse using contaminated loamy sand soil (polluted with Cd, Pb, Cu, and other metals) collected from a smelter-impacted area. Microplastics were added at a concentration of 70–80 mg/kg, and lettuce seedlings were grown under phytotron conditions (22 ± 2 °C, 60 ± 5% RH, 16 h light/8 h dark) without fertilizers or external contaminants. Plant roots and shoots were harvested, and heavy metals were analyzed via MP-AES and ICP-MS. The results showed that MPs altered heavy metal mobility, bioavailability, and plant uptake. Copper accumulation in leaves decreased substantially across MP treatments, from 80.84 mg/kg in the control to 26.35 mg/kg (glitter), whereas lead and cadmium concentrations increased significantly in roots under fiber and glitter exposure (Pb increased from 12.13 mg/kg to 33.57 mg/kg and Cd from 1.70 mg/kg to 2.05 mg/kg in fiber treatment). Cobalt accumulation in leaves increased under the plastic bag treatment, indicating MP-specific metal interactions. Root growth was also affected, with fibers promoting elongation and plastic bottles restricting it. Sequential extraction revealed that MPs modified metal partitioning in soil, with Pb and Ni more strongly retained in stable fractions under some treatments. Observed trends in soil pH and organic matter content were associated with changes in metal mobility, highlighting the potential role of soil properties in mediating microplastic–metal interactions. These findings highlight the role of MPs as mediators of heavy metal transport in crops and underscore the need for clear regulatory guidelines that limit microplastic contamination in agricultural soils and promote routine monitoring to safeguard food safety and crop health.